Large-Scale Fusion of Gray Matter and Resting-State Functional MRI Reveals Common and Distinct Biological Markers across the Psychosis Spectrum in the B-SNIP Cohort - Wang, Zheng; Meda, Shashwath A.; Keshavan, Matcheri S.; Tamminga, Carol A.; Sweeney, John A.; Clementz, Brett A.; Schretlen, David J.; Calhoun, Vince D.; Lui, Su; Pearlson, Godfrey D. (Frontiers in Psychiatry, 2015)
To investigate whether aberrant interactions between brain structure and function present similarly or differently across probands with psychotic illnesses (schizophrenia (SZ), schizoaffective disorder (SAD), and bipolar I disorder with psychosis (BP)) and whether these deficits are shared with their first-degree non-psychotic relatives. A total of 1199 subjects were assessed, including 220 SZ, 147 SAD, 180 psychotic BP, 150 first-degree relatives of SZ, 126 SAD relatives, 134 BP relatives and 242 healthy controls. All subjects underwent structural MRI (sMRI) and resting-state functional MRI (rs-fMRI) scanning. Joint independent analysis (jICA) was used to fuse sMRI gray matter (GM) and rs-fMRI amplitude of low frequency fluctuations (ALFF) data to identify the relationship between the two modalities. Joint ICA revealed two significantly fused components. The association between functional brain alteration in a prefrontal-striatal-thalamic-cerebellar network and structural abnormalities in the default mode network (DMN) was found to be common across psychotic diagnoses and correlated with cognitive function, social function and Schizo-Bipolar Scale (SBS) scores. The fused alteration in the temporal lobe was unique to SZ and SAD. The above effects were not seen in any relative group (including those with cluster-A personality). Using a multivariate fused approach involving two widely used imaging markers we demonstrate both shared and distinct biological traits across the psychosis spectrum. Further, our results suggest that the above traits are psychosis biomarkers rather than endophenotypes.